Effects of pre-existing discontinuities on the residual strength of rock mass – Insight from a discrete element method simulation. (April 2016) - Gao, F.Q.; Kang, H.P.
Abstract: When rock failure is unavoidable, the designer of engineering structures must know and account for the residual strength of the rock mass. This is particularly relevant in underground coal mine openings. Pre-existing discontinuities play an important role in the mechanical behavior of rock masses and thus it is important to understand the effects of such pre-existing discontinuities on the residual strength. For this purpose, the present study demonstrates a numerical analysis using a discrete element method simulation. The numerical results indicate that fracture intensity has no significant influence on the residual strength of jointed rock masses, independent of confining conditions. As confining pressures increase, both peak and residual strengths increase, with residual strength increasing at a faster rate. The finding was further demonstrated by analyzing documented laboratory compressive test data from a variety of rocks along with field data from coal pillars. A comprehensive interpretation of the finding was conducted using a cohesion-weakening-friction-strengthening (CWFS) model. The effect of rock bolts on rock mass strength was also evaluated by using a discrete element method model which suggested that rock bolts can significantly increases residual strength but have limited effect on increasing the peak strength of rock masses. Highlights: Investigate the influence of pre-existing discontinuities on the residual strength of jointed rock mass. Evaluate the effect of rock bolts on the strength of jointed rock masses. Propose a modified CWFS model interpreting why residual strengths increase at a faster rate than peak strengths.